Failure analysis of connecting rod - Andoko, A. (American Institute of Physics Inc., 2020)
Increasing the volume of combustible motor vehicles, needs to be anticipated as early as possible if there is a failure on the combustion engine components. Failure that may occur on the component is the connecting rod. This study aims to determine the cause of the failure of a connecting rod car. The method used in this study consisted of several tests namely, macro photographs, microstructure test, SEM/EDX and hardness test. The results show that the specimen is AISI 4315 with a hardness of 30.98 RC. The specimen has a hard surface but is resilient on the inside. This can be seen from the shape of the fault that has a lot of dimple, beachmark, and fracture folds. Â© 2020 American Institute of Physics Inc.. All rights reserved.